The influence of predictors on travel web site adoption among Malaysian travellers - Abd Aziz, N.; Musa, G.; Sulaiman, A. (Academic Journals, 2010)
A research framework of travel web site acceptance was developed based on technology acceptance model and theory of reasoned action. This study examined the influences of web site effectiveness characteristics, social factors and Internet self-efficacy on future intention to use travel web sites. From a multistage cluster sampling among employees in selected organizations in the Malaysian Klang valley, a total of 679 questionnaires were returned and analyzed. The results revealed significant influences of web site effectiveness characteristics and social factors on future intention to use travel web sites. Internet self-efficacy moderated negatively the influence of technical adequacy and system quality on future intention to use travel web sites. The paper highlights its theoretical, marketing and managerial implications.